STRUCTURING PEDAGOGICAL CONTENT PRACTICES OF STUDENTS BY SPECIALTY "PRESCHOOL EDUCATION" (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the structure of the content of the pedagogical the practice o f the student’s — of future tutors I-II courses pedagogical university, direct on the formation of the readiness for the upbringing of responsibility in the preschool children’s.